Methodological Challenges in Web-Based Qualitative Research With Medically Underserved Populations - Alexandra Malia Jackson; Juhee Woo; Marley Olson; Francis Dalisay; Pallav Pokhrel; Clemma J Muller; Scott K Okamoto (JMIR Publications, 2023)
Internet- or web-based research is rapidly increasing, offering multiple benefits for researchers. However, various challenges in web-based data collection have been illustrated in prior research, particularly since the onset of the COVID-19 pandemic. To add to the literature on best practices for web-based qualitative data collection, we present 4 case studies in which each research team experienced challenges unique to web-based qualitative research and had to modify their research approaches to preserve data quality or integrity. The first 2 case examples describe issues with using social media to recruit hard-to-reach populations, the third example demonstrates the challenge in engaging adolescents in sensitive conversations on the web, and the final example discusses both the issues in recruitment and the use of different modalities in collecting data to accommodate the medical needs of study participants. Based on these experiences, we provide guidance and future directions for journals and researchers in collecting qualitative data on the web.